Creating science and theology through a cultural lens - Viviers, Hennie (Old Testament essays, 2009)
Creating science and theology from a cultural perspective is not a choice but a constraint. Our human capacity to symbolise, to create symbolic worlds within which we live always remains within the ambit of culture. The two dominant cultural discourses of science and theology both endeavour to explain reality, albeit in different ways. Both inform the way in which we construe our world, hence the motivation for the complementing perspectives of the religion : science debate. If, for whatever reason, science does not comment on the meaning of life, it loses its status as "omniscience". If theology inclines to a kind of fictional supernaturalism, a faith experience of a culturally unmediated "more", it likewise becomes questionable. Science does not know all, and neither does theology know "more" than what culture / nature provides.